Basic Needs in the Year 2000 (The Pakistan Development Review, 1980)
The paper distills the main lessons of recent country and sector work on Basic needs approaches to development. It argues that, drawing on this experience and adopting appropriate policies, the basic needs of the world's poor can be met in a shorter period of time, and with fewer resources i.e. by the year 2000-than if the more conventional approach of relying solely on rising incomes is chosen. Raising the earning opportunities of the poor remains a central thrust of the strategy, but it has to be supplemented by actions in the public sector and within households.